The Effect of Pre-Task Planning Time on Second Language Oral Performance in Terms of Fluency & Accuracy on Saudis Female Preparatory Students at Princess Nora University - AL-Qahtani, Hind M. (Advances in Social Sciences Research Journal, 2016)
The study investigates the effects of pre-task planning time on both fluency, and accuracy and fluency of the participants' oral performance. The participants' performance has been transcribed and analyzed. The experimental group was provided with 5 minutes planning time before task performance whereas the control group was given a zero-planning time .As a result , the experimental group produces accurate language and fluency language input. The results of the study indicated that participants who performed the task under time pressure spoke significantly faster that those who had no time pressure during the task and the Participants with zero – planning time produced a greater variety of vocabulary than those who planned before the task. The pre –task Planning time reduces the processing load , helps learners to get goals and organize the content , reduces pressure to speak freely with self-confidence during the performance of the oral task , enhances the accuracy of the second language learner' production , concentrates more on form which helps to improve the accuracy of their second language production , and Planning time helps them to form and edit their oral production. The findings of the study are beneficial for English teachers , English designers and materials development.